Broadband near-infrared emission in barium gallo-germanate glasses co-doped with bismuth, chromium and erbium ions - Kochanowicz, Marcin; Markiewicz, Jakub (Photonics Letters of Poland, 2024)
This work presents barium gallo-germanate glasses co-doped with Bi+/Er3+ and Cr3+/Er3+ ions for NIR luminescence. The addition of Al2O3 content in the glass matrix made it possible to obtain luminescence corresponding to the 3P1→3P0 transition of Bi+ ions. Co-doping with the Bi+/Er3+ system resulted in a broad luminescence spectrum of 1.0-1.6 µm and Cr3+/Er3+ co-doping in selected glass matrix resulted in luminescence in 0.9-1.6 µm band. However, the luminescence of the Cr3+ ions is much lower than that of Er3+ ions. Full Text: PDF References T. Suzuki, G.S. Murugan, and Y. Ohishi, ’Optical properties of transparent Li2O-Ga2O3-SiO2 glass-ceramics embedding Ni-doped nanocrystals’, Appl. Phys. Lett., 86(13), 131903 (2005). CrossRef N.V. Golubev et al., ’Pre-crystallization heat treatment and infrared luminescence enhancement in Ni2+-doped transparent glass-ceramics’, J. Non-Cryst. Solids, 515, 42 (2019) CrossRef Z. Xu, W. Feng, T. Chen, X. Liu, and J. Qiu, ’Tuning optical properties in PbSe quantum dot-doped borosilicate glass fiber by modulation of network topology’, Opt. Laser Technol., 158, 108910 (2023). CrossRef M.A. Hughes, T. Suzuki, and Y. Ohishi, ’Spectroscopy of bismuth-doped lead-aluminum-germanate glass and yttrium-aluminum-silicate glass’, J. Non-Cryst. Solids, 356(44), 2302 (2010). CrossRef J. Song, Z. Zhou, B. Zhong, M. Zhang, J. Huang, and L. Han, ’Ultra-broadband near-infrared Cr3+-doped multi-phase glass-ceramics realized by the selective enrichment strategy for near-infrared spectroscopy applications’, J. Alloys Compd., 968, 172126 (2023). CrossRef M.A.U. Martines, M.R. Davolos, M.J. Júnior, D.F. de Souza, and L.A.O. Nunes, ’Cr3+ and Cr4+ luminescence in glass ceramic silica’, J. Lumin., 128(11), 1787 (2008). CrossRef S. Zhou, H. Dong, H. Zeng, J. Hao, J. Chen, and J. Qiu, ’Infrared luminescence and amplification properties of Bi-doped GeO2−Ga2O3−Al2O3 glasses’, J. Appl. Phys., 103(10), 103532 (2008). CrossRef T. Suzuki and Y. Ohishi, ’Ultrabroadband near-infrared emission from Bi-doped Li2O-Al2O3-SiO2 glass’, Appl. Phys. Lett., 88(19), 191912 (2006). CrossRef T. Minh Hau et al., ’Super broadband near-infrared emission and energy transfer in Bi-Er co-doped lanthanum aluminosilicate glasses’, Opt. Mater., 35(3), 487 (2013). CrossRef H.K. Dan et al., ’Effects of Y3+on the enhancement NIR emission of Bi+-Er3+ co-doped in transparent silicate glass-ceramics for Erbium-doped fiber amplifier (EDFA)’, J. Lumin., 219, 116942 (2020). CrossRef E.M. Dianov, ’Bismuth-doped optical fibers: a challenging active medium for near-IR lasers and optical amplifiers’, Light Sci. Appl., 1(5) (2012). CrossRef L. Wang, L. Tan, Y. Yue, M. Peng, and J. Qiu, ’Efficient Enhancement of Bismuth NIR Luminescence by Aluminum and Its Mechanism in Bismuth‐Doped Germanate Laser Glass’, J. Am. Ceram. Soc., 99(6), 2071 (2016). CrossRef Z. Jiang et al., ’Effects of Al2O3 composition on the near-infrared emission in Bi-doped and Yb-Bi-codoped silicate glasses for broadband optical amplification’, J. Non-Cryst. Solids, 383, 196 (2014). CrossRef